PULSE WAVE VARIABILITY WITHIN TWO SHORT-TERM MEASUREMENTS - Korpas, David; Halek, Jan (Biomedical papers, 2006)
Background: Pulse wave analysis permits non-invasive assessment of indices of arterial elasticity. Decreased arterial elasticity results in higher pulse wave velocity and therefore earlier wave reflection.Aim: The aim of this study was to evaluate the short-term variability for measurement of surface arteries.Method: For detection of artery wall movement, a plethysmography method was used. The changes in artery volume, affecting the fluid behind the scanning membrane, transfer themselves into pressure changes and move towards the positive input of a sensitive differential pressure transducer. The output is carried to a notebook computer and analysed within the frequency and time domain. To correlate arterial pulse waves, the following parameters were used: relative crest time RCT, interwave distance IWD, dicrotic wave amplitude DWA and dicrotic wave time DWT. These parameters were analysed using Bland-Altman plots.Results: Two data points (5.6 %) fall outside the 2*SD range for both IWD and DWA parameters on posterior tibial artery and one data point (2.8 %) for DWT. Three data points (8.3 %) fall outside the 2*SD range for IWD and two data points for both DWA and DWT on the radial artery. Two data points fall outside the RCT measured on the ulnar artery, and all but one for IWD, DWA and DWT lie within the 2*SD range.Conclusions: Pulse wave analysis showed reproducibility in a short-term study of all three measured distal arteries and is therefore suitable for use in patients for observing the progression of artery-wall-involving diseases.
Keywords: Pulse wave/Blood flow/Plethysmography/Arterial elasticity/Blood volume/ Measurement techniques